PENGEMBANGAN MODEL PEMBELAJARAN GETARAN BERBASIS VIDEO YOUTUBE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA POLITEKNIK - I Gede Rasagama (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2020)
This study aims to find out: (i) video-based vibration learning model from http://youtube.com to improve concept understanding; (ii) the feasibility of the learning model; and (iii) strengths and weaknesses of the learning model. Research using the R&D approach includes 4 phases. The results showed: (i) the learning model was divided into: preliminary phases, core activities, and closing phases, containing objectives, sequence of material, and discussion based on student questions; (ii) an expert assesses the model is correct in the category: "in scope of concept" and "truth of concept"; (iii) Students in the limited trials I and II, respectively, judging by the categories between:  "good enough and good ", and  "good and very good"; (iv) strength: the scope of the concept is comprehensive, easy to access and repeat, saves lecturers' power, and references to 1 sub-topic are available from several varied videos; (v) weaknesses: learning 1 sub topic is still in the form of file compilation, Indonesian language references are limited, and the purpose of learning videos is binding.